2017
DOI: 10.1021/acsmedchemlett.7b00258
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Potent and Selective RIPK2 Inhibitors for the Treatment of Inflammatory Diseases

Abstract: NOD2 (nucleotide-binding oligomerization domain-containing protein 2) is an internal pattern recognition receptor that recognizes bacterial peptidoglycan and stimulates host immune responses. Dysfunction of NOD2 pathway has been associated with a number of autoinflammatory disorders. To date, direct inhibitors of NOD2 have not been described due to technical challenges of targeting the oligomeric protein complex. Receptor interacting protein kinase 2 (RIPK2) is an intracellular serine/threonine/tyrosine kinase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
35
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(37 citation statements)
references
References 22 publications
2
35
0
Order By: Relevance
“…This is further revealed by the molecular docking of CSLP37 (R 1 = F) and CSLP43 (R 1 = OMe), which demonstrates that the larger R 1 groups of these molecules more optimally fill the deep pocket (Figs 3E and F,and EV2F). Notably, examining available crystal data, we observed that all previously reported inhibitors that potently antagonize NOD2 signaling, including GSK583, ponatinib, and the recently reported compound 7f (Canning et al, 2015;Nachbur et al, 2015;Najjar et al, 2015;Haile et al, 2016;He et al, 2017), all occupy the deep pocket ( Fig 3G).…”
Section: Development Of a New Series Of Potent Small Molecule Ripk2 Imentioning
confidence: 67%
See 1 more Smart Citation
“…This is further revealed by the molecular docking of CSLP37 (R 1 = F) and CSLP43 (R 1 = OMe), which demonstrates that the larger R 1 groups of these molecules more optimally fill the deep pocket (Figs 3E and F,and EV2F). Notably, examining available crystal data, we observed that all previously reported inhibitors that potently antagonize NOD2 signaling, including GSK583, ponatinib, and the recently reported compound 7f (Canning et al, 2015;Nachbur et al, 2015;Najjar et al, 2015;Haile et al, 2016;He et al, 2017), all occupy the deep pocket ( Fig 3G).…”
Section: Development Of a New Series Of Potent Small Molecule Ripk2 Imentioning
confidence: 67%
“…This mode of activity may also be relevant for other inhibitors since an alignment of published RIPK2 structures indicates that all potent inhibitors of NOD signaling such as ponatinib (Canning et al , ) and GSK583 (Haile et al , ) extend into the deep pocket occupied by R 1 ‐R 3 substituents of the CSLP series (Fig G). Another recently described ATP‐competitive RIPK2 inhibitor series with potent activity in cells (e.g., compound 7f) possesses a phenyl ring similar to the CSLP inhibitors (He et al , ). While this molecule lacks a group corresponding to the R 2 group in the CSLP series, it contains a pyridine and the crystal structure indicates the presence of a water molecule in place of R 2 in this case (Fig G).…”
Section: Discussionmentioning
confidence: 99%
“…19 A highly potent and selective inhibitor of RIP2 kinase, GSK583 10 nM (MedchemExpress, USA) was used to block the NOD2-RIPK2 pathway. 20 Then, the culture plates were gently shaken for 5 minutes. After stimulation, the supernatants and RNAiso Plus (TaKaRa)-treated cells were harvested.…”
Section: Cell Culture and Particle Stimulationmentioning
confidence: 99%
“…Comparison with Recently Identified RIPK2 Inhibitors. Recently, four inhibitors to RIPK2 were identified as OD36/OD38 (Tigno-Aranjuez et al, 2014) WEHI-435 (Nachbur et al, 2015), GSK-583 (Haile et al, 2016), and the one from Novartis (He et al, 2017). OD36 and OD38 were obtained through a small molecule macrocylization process from Oncodesign (Dijon Cedex, France) with IC 50 values of , 100 nM and the ability to interfere with MDP dependent RIPK2 activity.…”
Section: Discussionmentioning
confidence: 99%
“…This bound to the ATP binding pocket of the kinase domain and inhibited RIPK2 with an IC 50 of 5-50 nM, depending on the assay. Last, Novartis recently reported on their RIPK2 inhibitor, obtained by virtual screening of their proprietary library, that can inhibit RIPK2 with an IC 50 of 3 nM (He et al, 2017). No in vivo applicability was analyzed, but it can selectively inhibit MDPpromoted cytokine production in peripheral blood mononuclear cells and bone marrow-derived mouse macrophages.…”
Section: Introductionmentioning
confidence: 99%